Analysis of the Determination of Product Selling Price Using the Cost Plus Pricing Method (Case Study at UD Homebake Palembang) - Nyayu Yullia Hidayani; Endah Dewi Purnamasari; M. Kurniawan DP (International Journal of Community Service & Engagement, 2023)
This study aims to analyze the determination of the selling price set based on the cost plus pricing method compared to the selling price set by the company. This research was conducted at UD Homebake Palembang. The data used in this study were primary data obtained from interviews. The method used in this research is descriptive qualitative analysis. The results indicates that there were differences in determining the selling price at UD Homebake Palembang with the cost plus pricing method. This research is expected to help UD Homebake Palembang in determining the selling price of the product